Representing Sustainable Communication in Ecofashion Posters: A Multimodal Discourse Analysis of English Education Students' Works - Hasanul Misbah (Journal of Transdisiplinary Studies in Education, 2026)
Background: Sustainable communication is increasingly recognized as an important approach to promoting environmental awareness. However, limited research has examined how pre-service English teachers construct sustainability messages through multimodal learning activities. \ Aims: This study investigates how undergraduate English education students represent sustainable communication in ecofashion posters and explores the interaction between visual and verbal elements in conveying environmental messages. Methods: A qualitative design employing Multimodal Discourse Analysis (MDA) was adopted. Six ecofashion posters were purposively selected from projects produced by 180 students enrolled in six English education classes. The data were analyzed using a Multimodal Analytical Protocol integrating Kress and van Leeuwen’s Visual Grammar with Halliday’s Systemic Functional Linguistics. Results: Three major themes emerged: circular fashion and resource conservation, minimalist consumption through capsule wardrobes, and eco-literacy through digital content creation. The posters demonstrated coherent visual-verbal integration, combining material processes, imperative expressions, conceptual visual structures, and offer gazes to communicate sustainability as a practical and relatable lifestyle rather than a moral obligation. Conclusion: The findings suggest that multimodal composition activities can strengthen eco-literacy, multimodal competence, and critical communication skills. Integrating sustainability-oriented multimodal projects into English language education may provide meaningful opportunities for developing both language proficiency and environmental awareness.